Optical coherence tomography of the optic nerve head detects acute changes in intracranial pressure - Anand, Aashish; Pass, Anastas; Urfy, Mian Z.; Tang, Rosa; Cajavilca, Christian; Calvillo, Eusebia; Suarez, Jose I.; Venkatasubba Rao, Chethan P.; Bershad, Eric M. (Journal of clinical neuroscience, 2016)
•We performed optical coherence tomography (OCT) pre/post cerebrospinal fluid (CSF) drainage in pseudotumor cerebri patients.•We evaluated the immediate response of several anatomical features of the optic nerve head.•The RPE – BM angle became significantly more negative in all patients after CSF drainage.•This preliminary study suggests that acute changes in CSF pressure may be detectable by OCT. We aimed to determine if there are measurable objective changes in the optic nerve head (ONH) immediately after cerebrospinal fluid (CSF) drainage in a prospective case-series of five patients undergoing a clinically indicated lumbar puncture (LP) for diagnosis of idiopathic intracranial hypertension. A Cirrus high-definition optical coherence tomography machine (Carl Zeiss Meditec, Dublin, CA, USA) was used to acquire images in the lateral decubitus position. Optic disc cube and high-definition line raster scans centered on the ONH were obtained immediately before and after draining CSF, while the patient maintained the lateral decubitus position. Measured parameters included retinal nerve fiber layer (RNFL) thickness, peripapillary retinal pigment epithelium/Bruch’s membrane (RPE/BM) angulation, transverse neural canal diameter (NCD) and the highest vertical point of the internal limiting membrane from the transverse diameter (papillary height). The mean (±standard deviation) opening and closing CSF pressures were 34.3±11.8 and 11.6±3.3cmH2O, respectively. Mean RNFL thickness (pre LP: 196±105μm; post LP: 164±77μm, p=0.1) and transverse NCD (pre LP: 1985±559μm; post LP: 1590±228μm, p=2.0) decreased in all subjects, but with non-significant trends. The RPE/BM angle (mean change: 5.8±2.0degrees, p=0.003) decreased in all subjects. A decrease in papillary height was seen in three of five subjects (mean: pre LP: 976±275μm; post LP: 938±300μm, p=0.9). Our results show a measurable, objective change in the ONH after acute lowering of the lumbar CSF pressure, suggesting a direct link between the lumbar subarachnoid space and ONH regions, and its potential as a non-invasive method for monitoring intracranial pressures.